1980
DOI: 10.1002/art.1780230409
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adenosine triphosphatases by gold

Abstract: Inhibition of adenosine triphosphatase (ATPase) by chlorauric acid (Au3+) and gold sodium thiomalate (Au+) was studied in dog brain and kidney and in human kidney enzyme preparations. Au3+ indiscriminately affected ouabain‐sensitive (Na+ + K+‐dependent) ATPase and ouabain‐insensitive (Mg2+‐dependent) ATPase with concentrations for 50% inhibition (I50) approximately 10‐6 M. The I50 of Au3+ for Na+ + K+ ATPase was several‐fold higher in homogenates than in microsomal fractions. The enzyme was protected by bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…If ATPase is inhibited by a metallic ion such as cadmium, ciliary activity would be adversely affected. This would be reasonable in light of the data of Sugawara (28) and Nechay (29). Both investigators demonstrated that cadmium levels as low as 10' M significantly inhibited (Na+ + K+) ATPase and (Mge ') and (Mg2 + + Ca2 +) ATPase in animal tissues.…”
Section: Resultssupporting
confidence: 59%
“…If ATPase is inhibited by a metallic ion such as cadmium, ciliary activity would be adversely affected. This would be reasonable in light of the data of Sugawara (28) and Nechay (29). Both investigators demonstrated that cadmium levels as low as 10' M significantly inhibited (Na+ + K+) ATPase and (Mge ') and (Mg2 + + Ca2 +) ATPase in animal tissues.…”
Section: Resultssupporting
confidence: 59%
“…For half-maximal inhibition of the mic rosomal enzyme, similar concentrations ranging between 1.2 and 1.6 x 10 4M were noted for human [48], rat, rabbit, mouse, and sheep kidney and of 2.1 and 3.2 x 10 AM for cortex and outer medulla, respectively, of the dog and guinea pig kidney [49]. Mg-ATPase was approximately 10 times less sensitive to this metal (table IV).…”
Section: Discussionmentioning
confidence: 99%
“…Suggested mechanisms underlying the therapeutic efficacy ofthese drugs include the inhibition oflysosomal or other cellular enzymes (26)(27)(28), interference with complement activation (29,30), inhibition ofprostaglandin biosynthesis (31,32), alterations in protein interactions (33)(34)(35)(36) and sulfhydryl reactivity (37), and nonspecific antiinflammatory activity (38). It has also been suggested that they block the accessory cell functions of macrophages, leading to regression of cell-mediated immunological reactions (39).…”
Section: Discussionmentioning
confidence: 99%